Plasma levels of vasostatin-1, a chromogranin A fragment, are associated with carotid artery maximum stenosis: A pilot study. (1st June 2017) - Bachetti, Tiziana; Ferrari Bardile, Alberto; Aloi, Teresa Lucia; Colombo, Barbara; Assi, Emma; Savino, Giuseppina; Vercelli, Andrea; Colombo, Roberto; Corti, Angelo
Abstract: Background: Chromogranin A (CgA), a circulating protein released by the neuroendocrine system, can regulate vascular physiology and angiogenesis. Full-length CgA (CgA1–439 ) and its fragment CgA1–76 (called vasostatin-1, VS-1) preserve the physiological integrity of the endothelial barrier function and are antiangiogenic, whereas CgA1–373 is proangiogenic. We investigated whether these polypeptides are altered in patients with various degrees of carotid artery atherosclerosis. Methods: We studied 81 patients with carotid artery atherosclerosis, asymptomatic for cerebrovascular diseases. Carotid arteries were examined by Doppler ultrasound and plaque characteristics were recorded. Plasma levels of CgA1–439, VS-1, CgA1–373, and total-CgA (CgA1–439 plus truncated fragments lacking part or the entire C-terminal region) were assessed by specific ELISAs. Results: Plasma levels of VS-1 and total-CgA correlated with carotid artery maximum stenosis ( r  = 0.349, p  = 0.001 and r  = 0.256, p  = 0.021, respectively). Stepwise multiple regression analysis indicated that VS-1 was a significant predictor of maximum stenosis after adjustment for age, gender, and conventional risk factors for atherosclerosis (regression coefficient = 12.42, SE = 4.84, p  = 0.012). In addition, logistic regression analysis indicated that relatively high levels of full-length CgA, but not total-CgA, predict the presence of hypoechoic, lipid-rich plaques (OR = 1.47; 95% CI: 1.19–1.81, p  = 0.0003). Conclusion: VS-1 is independently associated with carotid artery maximum stenosis. Furthermore, full-length CgA is an independent indicator of hypoechoic plaques, likely reflecting initial stages of atherosclerosis. Given the known capability of CgA and VS-1 to regulate vascular function and angiogenesis these polypeptides might play a role in the regulation of atherosclerosis pathophysiology. Highlights: Chromogranin A and vasostatin-1 are increased in carotid artery atherosclerosis. Vasostatin-1 is an independent predictor of carotid artery maximum stenosis. Full-length chromogranin A is an independent indicator for hypoechoic lesions.